Terapi Kompres Hangat Untuk Menurunkan Nyeri Dada Pada Pasien Acute Coronary Syndrome Non-STEMI - Bayu Prasetyo; Nur Chayati; Sidiq Purnomo (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background: Acute Coronary Syndrome is a manifestation of ischemic heart disease that occurs when blood flow to the heart is disrupted, leading to oxygen deficiency. One of the symptoms that arises in patients with Acute Coronary Syndrome is chest pain. One effective non-pharmacological therapy in reducing chest pain in patients with Acute Coronary Syndrome is warm compress therapy. Objective: To analyse effect of applying warm compress therapy to alleviate chest pain in patients with Acute Coronary Syndrome Non-STEMI. Method: The method used in this study is a case report. The instruments used are nursing assessment with the PQRST approach and Pain Measurement Scale with warm compress intervention evaluated over 3x 24 hours. Results: The results of this case study show a decrease in pain scores from 6 to 4 on the first day, decreasing to 3 on the second day and further decreasing to 2 on the third day. Conclusion: Warm compress therapy is effective in relieving chest pain in patients with Non-ST Elevated Myocardial Infarction Acute Coronary Syndrome.